Una aproximación al estudio de los determinantes sociales de la maternidad adolescente en el Noreste Argentino en base al Censo 2010 - Cazado, Carla (2019)
The present work sought to consolidate an approach to the study of the social determinants of adolescent motherhood in the Northeast. More specifically, he examined comparatively the sociodemographic characteristics of adolescent mothers in relation to adolescents who are not mothers, to know the incidence of different social and individual components of vulnerability in adolescent motherhood in the region and explore the existence of differences in similar socio-economic contexts, outside the region. It was a descriptive analysis whose approach methodology implied a quantitative approach based on the use of secondary data from the National Population, Household and Housing Census 2010 of Argentina. The universe of study was composed of adolescents aged 15 to 19 who, in this census round, resided in the Northeast region and mentioned having at least one child born alive. The results obtained show a greater degree of vulnerability attributable to the condition of maternity during adolescence, but which cannot necessarily be attributed to maternity itself. In this sense, adolescent mothers have some differential sociodemographic characteristics that imply greater conditions of social and individual vulnerability.